Model Evapotranspirasi Pada Vegetasi Dengan Ketebalankanopi Yang Bervariasi - Yanto, Yanto (Jenderal Soedirman University, 2011)
Evapotranspiration plays important key role on hydrological cycle and water balance in water catchment.PenmannMonteithformula expresses evapotranspiration rate which is governed by available solar radiation, characteristics of vegetation represented by aerodynamic resistance and stomata resistance.Canopy layer density isa characteristic of vegetation that influence the amount of solar radiation transferred and received by layers withinand underneath canopy. This article will describe model of evapotranspiration using Penman-Monteith formula on vegetation with different canopy layer assuming the Leaf Area Index (LAI) is constant.The model is applied onthe vegetation with canopy layer (N) is 3 and 10. The result shows that evapotranspiration model using Penman-Monteith formula is able to estimate evapotranspiration rate with margin error less than 1%. Assuming LAI is constant, the differenceof canopy layer numberproduces insignificant effect to evapotranspiration rate. Testing the model using N=3 and N=10 results margin error less than 1% aswell.